Juridical Consequences of the Decisions of the International Labour Conference - Binet, Henri (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1952)
SummaryThe Author describes the International Labour Conference, as the "annual meeting of the Member States of the International Labour Office. " The I.L.O. has as purpose "to promote social justice in the interest of world peace.'' After a short analysis of the means at the disposal of this organization, the Author establishes the necessary distinctions between three types of decisions which the I.L.O. may reach: Resolutions, Recommendations and Conventions. He then emphasizes the characteristics of the obligation of the Member States towards conventions, discussing the rôle of public opinion and of the functions of boards of inquiry. The author gives considerable attention to the case of federated states such as Canada, who enjoy a privileged situation, as the legislative jurisdiction here on labour questions is not entirely confined to the central authority. The possible points of dispute are studied in conclusion as well as the eventual sanctions.